Molecular characterization of Vibrio cholerae O1 outbreak strains in Miri, Sarawak (Malaysia) - Radu, Son; Vincent, Micky; Apun, Kasing; Abdul Rahim, Raha; Benjamin, Patrick Guda; Yuherman, Unfound; Rusul, Gulam (Elsevier, 2002)
Bacterial resistance to various antimicrobial agents is common in area with high usage of antibiotics. In this study, the data on antimicrobial susceptibility patterns of Vibrio cholerae O1 from patients during an outbreak period was found to be high but variable rates of multidrug resistance. Thirty-two of 33 V. cholerae isolates harboured the tcp, ctx, zot and ace genes, suggesting their possible roles in the outbreak cases. We analyzed the molecular diversity of a total of 33 strains of V. cholerae O1 isolated from 33 patients between November 1997 and April 1998 using random amplified polymorphic DNA (RAPD) analysis. The 30 typable isolates could be separated into four major clusters containing 5, 17, 2 and 6 isolates, respectively. However, no particular RAPD pattern was predictive of a particular pattern of antibiotic susceptibility. The findings of this study showed that multiple clones seemed to be responsible for cases in the outbreaks in the study area.